Coping with Workplace Bullying among Front Line Employees: A cross-sectional study - Hassan, Nazirah (International Journal of Psychosocial Rehabilitation, 2020)
Bullying at work has recently been a growing concern by researchers and practitioners from various disciplines including psychology and management. This study examines the different types of coping strategies used by targets of workplace bullying. A sample of (N = 270) front-line employees from various organisations in the Klang Valley area participated in this cross-sectional study. The survey measures a number ofdifferent types of bullying behavioursviathe Negative Acts Questionnaire (NAQ-R) and the different types of coping using existing scales that measures how victims deal with bullying. Results show that almost three quarters of the respondents of the study have experience of being mistreated via person-related (73.7%) and work-related bullying behaviours (75.6%) while an average of 15% were victims of workplace bullying experiencing negative acts at least on a weekly basis if not daily. Results also show that self-doubt was significantly correlated to all three types of workplace bullying behaviours and that problem solving was negatively correlated with personal-related bullying (r = -.30**). Although, it was found that majority of the respondents tend to ignore the problem and problem solving was the least choice of their coping strategy. T-test results showed significant differences between gender where female utilised more passive coping [t(268) = -2.07, p = .040] and ignoring [t(268) = -2.93, p = .004] while male utilised more problem solving [t(268) = 2.33, p = .021]. Findings are further discussed in the article.